A Comparative Study of English and French Gender - Husnul Hotimah; Beny Hamdani; Dian Luthfiyati; Raudhatul Islam (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2021)
This article looks critically the comparison between English and French Gender. The problem that will be discussed in this article is: What kind of similarities and differences do they have in gender, especially in distinguishing male from female persons? The significance of the study are to get inputs on gender in English and French in order to improve their ability in understanding gender from both languages . One of the characteristics of Indo-European language is gender, which classifies nouns to express sex distinctions. The following discussion will deal with two forms of gender, natural and grammatical gender, and the ways of showing gender. From the linguistics analysis of English and French gender that has been done in this article and the comparison between them, it can be concluded that both languages have some differences and similarities in the application of gender. The differences are focused on the kinds of gender used, English uses natural gender while French uses grammatical gender. The use of grammatical gender makes French does not have neuter gender. So the inanimate objects are considered to have gender, masculine or feminine, and the ways of showing their gender are afforded by the use of article, le for masculine and la for feminine.